2018
DOI: 10.1590/1807-3107bor-2018.vol32.0006
|View full text |Cite
|
Sign up to set email alerts
|

Impact of aggressive periodontitis and chronic periodontitis on oral health-related quality of life

Abstract: The purpose of this cross-sectional study was to investigate the effect of different forms of periodontal diseases on Oral Health-Related Quality of Life (OHRQoL). Fifty-two patients with Aggressive Periodontitis (AP) or Chronic Periodontitis (CP) were included: nine patients with Localized Aggressive Periodontitis (LAP), thirty-three patients with Generalized Aggressive Periodontitis (GAP) and ten patients with Generalized Chronic Periodontitis (GCP). Oral Health Impact Profile questionnaires (OHIP-14) were d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
36
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(50 citation statements)
references
References 27 publications
2
36
0
4
Order By: Relevance
“…A further similarity to the available literature is the missing association between oral health and OHRQoL for the patients within the current study, which has been repeatedly described and was hypothesized accordingly [8][9][10][11][12][13][14][15]. The nearly unaffected OHRQoL of the HTx and HF patients despite the high prevalence of periodontal treatment need in the current study is conspicuous, especially considering the effects of periodontitis on OHRQoL in generally healthy individuals [27]. Thus, the periodontal treatment need of the general population in Germany has to be mentioned.…”
Section: Comparison With Published Datasupporting
confidence: 70%
See 2 more Smart Citations
“…A further similarity to the available literature is the missing association between oral health and OHRQoL for the patients within the current study, which has been repeatedly described and was hypothesized accordingly [8][9][10][11][12][13][14][15]. The nearly unaffected OHRQoL of the HTx and HF patients despite the high prevalence of periodontal treatment need in the current study is conspicuous, especially considering the effects of periodontitis on OHRQoL in generally healthy individuals [27]. Thus, the periodontal treatment need of the general population in Germany has to be mentioned.…”
Section: Comparison With Published Datasupporting
confidence: 70%
“…Accordingly, the results of the patients in the current study match the unaffected or slightly reduced OHRQoL of patients with chronic diseases and conditions. Thus, the scale of reduction of the OHRQoL in these patients is far smaller than that for generally healthy patients who suffer from oral diseases such as generalized periodontitis or temporomandibular disorders [27,28].…”
Section: Comparison With Published Datamentioning
confidence: 94%
See 1 more Smart Citation
“…Higher scores of the GCP group could be related to the higher average age of the patients and the higher percentage of the smokers in this group. Conversely, Llanos et al reported no significant differences in functional limitation and social disability subscale in GAP and GCP patients. In their study, only psychological discomfort subscale score was higher in GCP patients than in GAP patients.…”
Section: Discussionmentioning
confidence: 91%
“…In their study, only psychological discomfort subscale score was higher in GCP patients than in GAP patients. Furthermore, Llanos et al reported that patient with GCP or GAP showed poorer OHRQoL than those with localized aggressive periodontitis (AP). This may be due to the fact that the localized form of AP is less disturbing for patients because it affects a more limited area than the generalized form.…”
Section: Discussionmentioning
confidence: 99%